Ten-word tiny tales : to inspire and unsettle - Coelho, Joseph (Candlewick Press, 2023)
UK Children's Laureate Joseph Coelho presents twenty tiny tales -- each one illustrated by a different artist, and each just ten words long -- in a book that's as much a work of art as an invitation to budding writers. Is it possible to spin a tale using just ten words? In this magnificent compendium, author and poet Joseph Coelho proves that it is -- with mini-stories of underwater worlds, demon hamsters, bears in outer space, and portals to places unknown. From charming to creepy, fantastical to mysterious, each tale is paired with an outstanding illustrator, and together words and pictures inspire creativity as young readers are prompted to continue the story. Prefaced with a note from the author and offering two writing challenges at the end, this is an ideal gift for anyone ready to unleash their imagination.